THE DETERMINANTS OF ADVANTAGES IN OPERATIONAL COMPANIES - Elwisam; Suadi Sapta Putra; Rahayu Lestari; Kumba Digdowiseiso; Nur Aishah Awi (Journal of Accounting Research, Utility Finance and Digital Assets, 2024)
The objective of this study is to examine the factors that contribute to a company's operational excellence using a Systematic Literature Review (SLR) methodology. The research background is motivated by a profound desire to comprehend the factors that have a substantial impact on a company's operational performance. The systematic literature review (SLR) approach was employed to examine scientific literature pertaining to the factors influencing operational excellence, thereby ensuring a methodical and unbiased study. The analysis reveals that company size, company age, and capital volume growth exert a positive and substantial impact on operational excellence. Simultaneously, the growth of investments has had an adverse effect, underscoring the importance of cautious investment management. The impact of leverage (debt ratio), tabarru' funds, and independent commissioner ratio on operational excellence is not always significant. Ultimately, a comprehensive comprehension of these factors offers valuable direction for companies in formulating efficient and flexible operational strategies. This study provides a substantial contribution to the existing body of knowledge on operational management. It emphasizes crucial factors that companies must take into account to enhance their efficiency and competitiveness. Furthermore, these discoveries establish a foundation for additional investigation and serve as a valuable resource for company executives seeking to enhance their operations amidst constantly shifting market dynamics.